Gamma camera imaging for studying intestinal absorption and whole-body distribution of selenomethionine. Issue 3 (9th August 2013) - Madsen, Jan L.; Sjögreen-Gleisner, Katarina; Elema, Dennis R.; Søndergaard, Lasse R.; Rasmussen, Palle; Fuglsang, Stefan; Ljungberg, Michael; Damgaard, Morten
Abstract : Se metabolism in humans is not well characterised. Currently, the estimates of Se absorption, whole-body retention and excretion are being obtained from balance and tracer studies. In the present study, we used gamma camera imaging to evaluate the whole-body retention and distribution of radiolabelled selenomethionine (SeMet), the predominant form of Se present in foods. A total of eight healthy young men participated in the study. After consumption of a meal containing 4 MBq [ 75 Se]l -SeMet ([ 75 Se]SeMet), whole-body gamma camera scanning was performed for 45 min every hour over a 6 h period, every second hour for the next 18 h and once on each of the subsequent 6 d. Blood, urine and faecal samples were collected to determine the plasma content of [ 75 Se]SeMet as well as its excretion in urine and faeces. Imaging showed that 87·9 (sd 3·3) % of the administered activity of [ 75 Se]SeMet was retained within the body after 7 d. In contrast, the measured excretion in urine and faeces for the 7 d period was 8·2 (sd 1·1) % of the activity. Time–activity curves were generated for the whole body, stomach, liver, abdomen (other than the stomach and the liver), brain and femoral muscles. Gamma camera imaging allows for the assessment of the postprandial absorption of SeMet. This technique may also permit concurrent studies of organ turnover of SeMet.